Польська освітня система у період структурних змін після 1989 року - стратегії і завдання (польською мовою) - Ева Вішнєвська (Pavlo Tychyna Uman State Pedagogical University, 2013)
У статті висвітлені завдання і стратегії модернізації польської системи освіти унаслідок структурних змін після 1989 року. Освіта представлена як інвестиція в розвиток суспільства. Значну увагу приділено висвітленню положень Стратегії розвитку системи освіти в Польщі на 2007-2013 рр., засадничим завданням якої є підготовка молодого покоління до участі в культурному, економічному суспільному житті у локальному, національному і глобальному вимірах. В статье освещены задачи и стратегии модернизации польской системы образования вследствие структурных изменений после 1989 года. Образование представлено как инвестиция в развитие общества. Значительное внимание уделено освещению положений Стратегии развития системы образования в Польше на 2007-2013 гг, основополагающей задачей которой является подготовка молодого поколения к участию в культурной, экономической общественной жизни в локальном, национальном и глобальном измерениях. Modernizing the Polish education system has always been an indispensible investment into the development of the society, especially, the young generation of Poles. Education systems must respond adequately to changes in the world, develop and improve constantly. The Strategy for Development of Education 2007-2013 states that education is to facilitate personal development as well as fulfilling everyone's goals, it is to prepare everyone to participate actively and responsibly in social, cultural and economic life - locally, nationally and globally. Also, it is to prevent exclusion and marginalization of individuals and social groups, respond quickly and flexibly to changes connected with the development of education, technology and globalization, adjust to changes in the job market.